«Sketches of Machining a Body Part in the Corel Draw Program Environment» - Rakhmonaliugli, Tukhtamirzaev Ulugbek; Farkhodugli, Umaraliev Abdulkhamid (Research Parks Publishing LLC, 2022)
The article describes the Part of the body, its design and method of obtaining. And described a short project for machining a part, created in the Corel Draw environment.